The advertisement calls of two species of Brachycephalus (Anura: Brachycephalidae) from southern Atlantic Forest, Brazil - De Carli Monteiro, Juliane Petry [UNESP]; Condez, Thais Helena [UNESP]; De Anchietta Garcia, Paulo Christiano; Baptista Haddad, Celio Fernando [UNESP] (Magnolia Press, 2018)
The advertisement calls are known for only eight species within the genus Brachycephalus. Herein, we describe the advertisement calls of B. olivaceus and B. quiririensis, both species from southern Atlantic Forest, state of Santa Catarina, Brazil. The advertisement calls of these species are similar, composed by one short and high-frequency note. The parameters range overlap between calls, as exemplified by the dominant frequency of 6.4-7.0 kHz in B. olivaceus and 6.2-6.5 kHz in B. quiririensis. Additionally, we provide a compilation of the available bioacoustic information for this genus.
Keywords: Bioacoustics; Brachycephaloidea; note-centered approach; pumpkin toadlets